Capturing carbon dioxide through a gas hydrate-based process - Partoon, B. (Italian Association of Chemical Engineering - AIDIC, 2015)
Gas hydrate based technology is one of new promising methods for capturing carbon dioxide. The carbon dioxide hydrate is a green compound which does not have any impact on the environment and the process is assumed to be less energy intensive. However, the development of gas hydrate based technology is suffering from slow formation rate and long induction time and endothermic nature of gas hydrate formation. In this article, a process based on gas hydrate technology is introduced for capturing of carbon dioxide from gaseous stream. The heart of this process is a new gas hydrate crystallizer which is designed especially for enhancing the hydrate formation rate. A series of semi-batch process is performed to investigate the performance of this setup for capturing carbon dioxide from a high carbon dioxide content methane-carbon dioxide gas mixture. Results indicated that new crystallizer has the ability to significantly reduce the induction time, increase the formation rate and overcome to the generated heat problem. Furthermore, it shows that pressure has the highest influence on formation rate and separation efficiency of the process among the studied parameters. Copyright Â© 2015, AIDIC Servizi S.r.l.,.